Influence of Psychiatric Medications on Neonatal Abstinence Syndrome in Women Treated for Opioid Use Disorder [17E]. (May 2020) - Staszewski, Cara; Herrera, Kimberly; Persad, Malini D.; Garretto, Diana; Davis, Jay; Garry, David
Abstract : INTRODUCTION: This study sought to evaluate the impact of prescribed psychiatric medications on newborn hospital stay in women undergoing treatment for opioid use disorder (OUD). METHODS: A cohort of women receiving either methadone or buprenorphine in management of OUD in pregnancy were identified from delivery and newborn records over a 10-year period. Women were excluded with delivery <24 weeks, multiple gestation or known anomalous fetus. Maternal demographics, medications, GA, mode of delivery, BW, NICU admission, newborn length of stay, NAS and treatment requirements for NAS were obtained. The study was IRB approved and standard statistics were used with a P -value of <0.05 considered significant. RESULTS: There were 180 women were identified with 101 (56%) receiving methadone and 79 (44%) receiving buprenorphine therapy. The groups were similar for age, parity, race, BMI, marital status, tobacco use, prenatal care, incidence of preterm birth, mode of delivery, and also had similar incidence of NAS (meth 91% vs bup 90%; P =.47). Buprenorphine users had a greater number of women prescribed psychiatric medications (meth 13% vs bup 35%; P <.001), higher GA at delivery (meth 37+2.8 wk vs bup 39+1.8 wk; P <.001), shorter newborn hospital stay (meth 14+10 d vs bup 9+8 d; P <.001) and fewer newborns with NAS requiring treatment (meth 56% vs bup 24%; P <.001). Psychiatric medication usage demonstrated a 4-fold likelihood of a longer newborn hospital stay (>10 d) and buprenorphine a shorter newborn stay. CONCLUSION: Psychiatric medication usage is an independent predictor of a longer newborn hospital stay in women undergoing treatment for opioid use disorder.